Analysis of Borax in Yellow Wet Noodles using Butterfly Pea Flower Extract (Clitoria ternatea) - Frizka Auliya; Diah Ariana; Baterun Kunsah (Health Notions, 2022)
One of the most popular foods is noodles. To get delicious noodles, often added food additives such as borax. Consuming foods that contain borax, will be at risk of serious health problems, it can even cause death. The purpose of this study was to determine the presence of borax in yellow wet noodles using butterfly pea flower (Clitoria ternatea) extract as an indicator. This type of research was descriptive study. The population was yellow wet noodles which were sold in the Lakarsantri area of West Surabaya. Sample was obtained from 10 sellers of yellow wet noodles in Lakarsantri. The borax testing method with a qualitative test of butterfly pea flowers (Clitoria ternatea) extract. The results found that 6 out of 30 samples (20%) were positive for borax, while 24 out of 30 samples (80%) did not contain borax. In conclusion, in this area, there are still yellow wet noodles that contain borax. Keywords: wet noodles; borax; butterfly pea flower; extract